Support service landscape as a key strategic driver in the actual knowledge economy of spanish higher education institutions - Perez-Encinas, Adriana; Rodriguez-Pomeda, Jesus (Revista Hipótese, 2017)
Globalization and internationalization have a complex relationship, but, for universities foreign student mobility is clearly related to both concepts. This student flows generates a large cross-border market, as well as a set of transformations in host and home universities. In this paper, we reflect on support services landscape in a Spanish Higher education context. Credit mobility flows are predominant in Spain, even though Spanish Higher education market continues to be welcoming and attractive to different type of mobile students from different countries worldwide.